Burden of allergy diets in Finnish day care reduced by change in practices. Issue 10 (6th May 2016) - Erkkola, M.; Saloheimo, T.; Hauta‐alus, H.; Kukkonen, A. K.; Virta, S.; Kronberg‐Kippilä, C.; Vaara, E.; Pelkonen, A. S.; Fogelholm, M.; Mäkelä, M. J.; ,
Abstract: Background: Nonessential allergy diets in children with mild symptoms may harm the development of immunological tolerance and impose a burden on families and day care. We aimed to reduce the high prevalence of allergy diets in day care by reforming the practices for inquiring about need of special diets from parents. Methods: We developed a new special diet form and an information leaflet based on the new allergy guidelines. The new form was implemented into 40 Finnish day care centres in the capital region in 2013–2015. The questionnaires on practices concerning special diets in day care centres and allergy knowledge were collected from the personnel. Results: After 2 years, the new special diet form was used by 64% of families with food‐allergic children, and the prevalence of allergy diets in day care centres decreased by 43% to 4.3% (IQ range 3.05–5.96). A significant decrease was found in the prevalence of all basic (milk, grains, egg) and most other allergy diets ( P for trend < 0.01). The new practice was well accepted by day care and kitchen personnel. Lack of updated allergy knowledge was noted among day care personnel. Conclusions: The burden of allergy diets in day care settings could be decreased by simple pragmatic changes based on current allergy guidelines. Old allergy attitudes persisted among day care personnel, indicating the need for continuous education.